Study of dynamic hole-forming performance of a cup-hanging planter on a high-speed seedling transplanter - Yang, Qizhi; Zhang, Ruoyu; Jia, Cuiping; Li, Zhangyan; Zhu, Menglan; Addy, M. (Frontiers in Mechanical Engineering, 2022)
Due to the advantages of hole-forming and transplanting at the same time even on a film covered field ridge, the cup-hanging transplanter has become one of the most widely used transplanter in agricultural operation. The cup-hanging planter is the main operating part of the transplanter. Different shapes of the hanging cup can affect the soil action mechanism, cavitation performance and planting quality. In this paper, the discrete element simulation software EDEM and the multi-body system dynamics analysis software RecurDyn are used to carry out the coupling simulation analysis. The results showed that the planting holes formed by hanging cups with two different shapes and under four different planting frequencies are all met the planting requirements. After soil reflow, the transverse dimensions of the two holes are similar and the longitudinal dimensions of the hole of the conical hanging cup are smaller than those of the quadrangular pyramidical hanging cup. Under the same planting frequency, the tear film size and hole-forming performance of the conical cup were better than that of the quadrangular pyramidical hanging cup. The result of simulation test is consistent with that of bench test, which proved the feasibility of using EDEM-RecurDyn coupling simulation to predict the hole-forming characteristics of the cup-hanging planter. The filmless hole-forming performances of two different shapes of hanging cups are close to each other. In terms of the film damage of film hole-forming, the conical cup is better than that of quadrangular pyramidical hanging cup.